Borderland Histories: The Archaeological Survey of Koya/Koisanjaq (2016-2022) From Local Chronology to Imperial Periodization: The Koya Region, Paleolithic to Parthian - Pappi, Cinzia; Coppini, Costanza; Awmar, Nyaz Azeez (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2025)
The Archaeological Survey of Koya/Koisanjaq (ASK) Project (2016-2022) examined an exemplar borderland between Mesopotamia and the Zagros through remote sensing, systematic surface investigations, and anthropological interviews, combined with stratified evidence from Satu Qala (ancient Idu). To date, the fieldwork has recorded 90 archaeological sites, ranging from small hamlets to medium-sized mounds, with materials dating from the Neolithic to the Islamic periods. This paper focuses on the regional settlement processes from the Paleolithic to the Parthian, characterized by phases of political expansion and contraction. Preliminary analysis of the surface collections reveals parallels with adjacent areas but underscores the need for a refined local chronology, which is currently being developed through excavations at Qala Shila. The results establish the Koya region as a dynamic landscape and an integral part of Mesopotamian historical trajectories.